DETERMINANTS OF LOCAL DEVELOPMENT STRATEGIES - Wiatrak, Andrzej (Acta Scientiarum Polonorum. Oeconomia, 2018)
The article seeks to specify the extent to which municipal development strategies form the basis for municipality development and what determines these strategies and development processes at the local level. It discusses the following issues: the nature and objectives of local development strategies, characteristics of the development strategy in the Stara Błotnica Municipality in the Mazowieckie Voivodship, and the determinants of the municipality’s local development strategy. The considerations herein suggest that the foundation for actions and the use of its resources is provided, on the one hand, by its multifunctional development and, on the other, by sustainable development, relying chiefly on its resources and support from various aid funds, in particular the European Union funds. The municipal development path is set in line with the socio- -economic policy implemented by higher levels, namely the EU, Poland, the Mazowieckie Voivodship and the Białobrzeski District. Task performance requires financial outlays that exceed the municipality’s budget, which proved to be a barrier to full implementation of the strategy. The article was prepared on the basis of related literature as well as documents and materials concerning the Stara Błotnica Municipality in the Mazowieckie Voivodship.